Overcoming reading anxiety using comic book (pop-art) reading material / Nurul Sofia Ahmad Fuad - Ahmad Fuad, Nurul Sofia (Faculty of Education, 2010)
This research is carried out as a survey on the first semester English 1 students of Universiti Tun Abdul Razak (UNIRAZAK). It investigated on the matter of overcoming reading anxiety using comic book (pop-art) reading material. The purpose of this study is to identify the factors that led students to experience reading anxiety and the effectiveness of using comic book (pop-art) as a reading material for students to overcome their anxiety in reading. A survey was conducted and data was collected via questionnaire and interview. The questionnaires were distributed to the students to obtain information needed for this study. Based on the findings, the study revealed that majority of the respondents preferred to read comic book (pop-art) as a reading material in order to help them overcome their anxiety in reading. Besides that, majority of the respondents obtained higher achievement in the post-test which was conducted using the comic book as the reading passage. Additionally, data from the interviews done on the educators have shown that majority agreed on the use of comic book as an optional source of reading material to help learners overcome their anxiety in reading. Many insights and suggestions regarding the issues have been addressed by both groups of respondents that contribute to the betterment of the study.